The Effect of Compensation on Employee Performance on PT. Waskita Beton Precast TBK - Zalne, Ziola; Albani, Muhammad Hudzaifa; Tanty, Heruna (Bina Bangsa International Journal of Business and Management, 2023)
This study aims to analyze the effect of Compensation on employee performance of PT.  Waskita Beton Precast, Tbk. There is an independent variable of the effect of Compensation to be tested for the influence on the dependent variable, namely Karyawa Performance.  The population in this study were employees of PT. Waskita Beton Precast, Tbk Human Resources division which has 50 employees as of May 2020, which are all permanent employees. The research data used are primary data obtained through the dissemination of questionnaires. The analysis tool used is a simple linear regression test. The results showed that: (1) the results showed that compensation had a positive and significant effect  on employee performance with a  significance value of 0.022 < 0.05; (2) the test results   of the coefficient of determination showed that the  Adjusted R Square  value of  0.579 means that as many as 57.9% of employee performance-bound variables can be explained by  the free variable, namely compensation,  while other  factors of  42.1% were influenced by  other variables outside the  variables studied